Sliding mode control strategy based lead screw control design in electromechanical tracking drive system - Tran Duc Chuyen; Van Hai Nguyen; Phuong Nam Dao; Nguyen Anh Tuan; Nguyen Van Toan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This article presents the research synthesis method of electromechanical tracking system for lead screw control using alternating current (AC) servo motors applied in machine tools, based on the framework of sliding mode control method and the state observer. Control algorithms are capable of compensating for perturbation components, with a state observation to be established to evaluate and compensate for uncertain nonlinear components. The chattering reduction techniques of sliding mode surface are proposed to improve the control effectiveness. The research results are verified by simulation on MATLAB-Simulink, showing that the proportional integral derivative (PID) controller has not met the control quality, but requires the sliding mode control law and state observation as proposed. Then this tracking drive system will work with better quality and can be developed for lead screw system of machine tool. The research results in the paper are also the completed development for calculating, designing, and manufacturing intelligent electrical drive systems in industrial applications.